Urgensi Perlindungan Hukum Bagi Korban Kecelakaan Lalu Lintas Menurut Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Ari Dermawan (Universitas Medan Area, 2020)
This paper presents legal protection for victims of traffic accidents as regulated in Law No. 22 of 2009 concerning Road Traffic and Transportation. The purpose of this study is the form of Legal Protection for Traffic Victims According to Law Number 22 Year 2009 Concerning Traffic and Road Transportation and Procedures for obtaining the Right to Victims of Traffic Accidents. This research method is a normative juridical approach using data obtained through library research, namely legislation, books, papers and other documents relating to this research and the website. The results obtained by Law Number 22 Year 2009 Concerning Traffic and Road Transportation in Article 240 states that victims of traffic accidents are entitled to get help and treatment from those responsible for traffic accidents and / or the government. responsible for the occurrence of traffic accidents, and compensation for traffic accidents from insurance companies.